Coral reefs - Ruiz de Larramendi, Alberto (Chicago : Childrens Press, 1993)
Discusses the habits of coral polyps, the formation of various types of coral reefs, associated plant and animal life, and the challenge of conservation.
Includes index.
Appraisal-Science Books for Young People.
7.2
5-8
Keywords: Coral reef biology -- Juvenile literature; Coral reefs and islands -- Juvenile literature; Corals -- Juvenile literature; Coral reef biology; Coral reefs and islands; Corals; Coral reefs and islands; Corals